DETERMINATION AND DEMARCATION OF FATIGUE CRACK INITIATION PHASE IN ROTATING BENDING CONDITION - Pasha, R. A.; Rehman, K.; Shah, M. (The Nucleus, 2012)
In engineering applications, components often experience cyclic loading and therefore, have crack initiation propagation phase. In this research work experimental demarcation of fatigue crack initiation has been investigated. Initiation phase of fatigue life of Aluminium was determined by using single and two step fatigue loading test on four point rotating bending fatigue testing machine. Experimental data is used to determine the distinction between the initiation and propagation phase. Initiation phase is determined at different stress levels. The obtained results demonstrate the effect of stress level on initiation phase and propagation phase.